Registry cost description of carpal tunnel release in Finland in 2011–2015 - Paulus Torkki; Aarni Hannula; Laura Miettinen; Kaisa Lampainen; Jorma Ryhänen; Sina Hulkkonen (BMJ Open)
Objectives In this study, we evaluated the amount of public funds spent on the operative treatment of carpal tunnel syndrome (CTS) in Finland in 2011–2015.Design A registry-based cost burden study.Setting The data were collected in primary and secondary care in both private and public hospitals, covering the whole population of Finland.Participants We collected the total number of patients with new CTS diagnoses and the total number of patients undergoing surgery from the Care Register for Health Care, Finland’s national register.Interventions Open carpal tunnel release (OCTR).Outcome measures We collected the costs of the OCTR procedure from diagnosis-related group prices. The Social Insurance Institution of Finland provided the total amount of euros reimbursed for sick leaves. We then combined the average amount of reimbursed sick leave with our estimated cost of the treatment chain to approximate the average cost per patient.Results The average amount of public funds used for diagnosing and surgically treating new CTS in 2011–2015 in Finland, including reimbursements for sick leaves, was €2759 per patient in 2015 currency. The average direct procedure cost was €1020. We found no clear trend in total cost per patient, but the proportion of surgically treated patients rose from 63.14% to 73.09%. The total annual cost of these treatments was between €18 128 420 and €22 569 973.Conclusions The average amount of public funds used to surgically treat one patient with new CTS in 2011–2015 in Finland was €2759, making the total annual burden €20.7 million.